System level analysis of cacao seed ripening reveals a sequential interplay of primary and secondary metabolism leading to polyphenol accumulation and preparation of stress resistance. (5th August 2016) - Wang, Lei; Nägele, Thomas; Doerfler, Hannes; Fragner, Lena; Chaturvedi, Palak; Nukarinen, Ella; Bellaire, Anke; Huber, Werner; Weiszmann, Jakob; Engelmeier, Doris; Ramsak, Ziva; Gruden, Kristina; et al.
Significance Statement: Cacao and its popular product, chocolate, have potential health benefits, with metabolites with anti‐oxidant and anti‐depressant effects, and which inhibit platelet aggregation and obesity‐dependent insulin resistance. Here we used proteomics and metabolomics to investigate cacao seed ripening and thus elucidate the underlying developmental controls of these biochemical processes. Summary: Theobroma cacao and its popular product, chocolate, are attracting attention due to potential health benefits including antioxidative effects by polyphenols, anti‐depressant effects by high serotonin levels, inhibition of platelet aggregation and prevention of obesity‐dependent insulin resistance. The development of cacao seeds during fruit ripening is the most crucial process for the accumulation of these compounds. In this study, we analyzed the primary and the secondary metabolome as well as the proteome during Theobroma cacao cv. Forastero seed development by applying an integrative extraction protocol. The combination of multivariate statistics and mathematical modelling revealed a complex consecutive coordination of primary and secondary metabolism and corresponding pathways. Tricarboxylic acid (TCA) cycle and aromatic amino acid metabolism dominated during the early developmental stages (stages 1 and 2; cell division and expansion phase). This was accompanied with a significant shift of proteins from phenylpropanoid metabolism to flavonoid biosynthesis. At stage 3 (reserve accumulation phase), metabolism of sucrose switched from hydrolysis into raffinose synthesis. Lipids as well as proteins involved in lipid metabolism increased whereas amino acids and N‐ phenylpropenoyl amino acids decreased. Purine alkaloids, polyphenols, and raffinose as well as proteins involved in abiotic and biotic stress accumulated at stage 4 (maturation phase) endowing cacao seeds the characteristic astringent taste and resistance to stress. In summary, metabolic key points of cacao seed development comprise the sequential coordination of primary metabolites, phenylpropanoid, N‐ phenylpropenoyl amino acid, serotonin, lipid and polyphenol metabolism thereby covering the major compound classes involved in cacao aroma and health benefits.